Very Low–Calorie Diet Mimics the Early Beneficial Effect of Roux-en-Y Gastric Bypass on Insulin Sensitivity and β-Cell Function in Type 2 Diabetic Patients - Jackness, Clifton; Karmally, Wahida; Febres, Gerardo; Conwell, Irene M.; Ahmed, Leaque; Bessler, Marc; McMahon, Donald J.; Korner, Judith (Diabetes (New York, N.Y.), 2013)
Marked improvement in glycemic control occurs in patients with type 2 diabetes mellitus shortly after Roux-en-Y gastric bypass surgery (RYGB) and before there is major weight loss. The objective of this study was to determine whether the magnitude of this change is primarily due to caloric restriction or is unique to the surgical procedure. We studied eleven subjects who underwent RYGB and fourteen subjects mean-matched for BMI, HbA1c, and diabetes duration who were admitted to our inpatient research unit and given a very low–calorie diet (VLCD) of 500 kcal/day with a macronutrient content similar to that consumed by patients after RYGB. Frequently sampled intravenous glucose tolerance tests were performed before and after interventions. Both groups lost an equivalent amount of weight over a mean study period of 21 days. Insulin sensitivity, acute insulin secretion after intravenous glucose administration, and β-cell function as determined by disposition index improved to a similar extent in both groups. Likewise, changes in fasting glucose and fructosamine levels were similar. Based on these data, VLCD improves insulin sensitivity and β-cell function just as well as RYGB in the short term.